2005
DOI: 10.1246/cl.2005.1344
|View full text |Cite
|
Sign up to set email alerts
|

Self-aggregation of Synthetic Zinc 3-Hydroxymethyl-purpurin-18 and N-Hexylimide Methyl Esters in an Aqueous Solution as Models of Green Photosynthetic Bacterial Chlorosomes

Abstract: Zinc 31-hydroxy-131-oxo-chlorins possessing a six-membered exo-ring attached at the 13- and 15-positions were prepared by modifying purpurin-18. These synthetic anhydride and imide self-aggregated in an aqueous THF solution to give large oligomers (J-aggregates) similarly with the corresponding natural and artificial chlorophylls possessing a five-membered E-ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…A small shoulder peak at around 560 nm might be induced from the Qx transition. These indicated that 13-CO- 2 self-aggregated in the aqueous micellar solution to make chlorosomal J -aggregates, similar to the self-aggregation of natural and synthetic chlorosomal chlorophylls. , ,,,,,,, …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…A small shoulder peak at around 560 nm might be induced from the Qx transition. These indicated that 13-CO- 2 self-aggregated in the aqueous micellar solution to make chlorosomal J -aggregates, similar to the self-aggregation of natural and synthetic chlorosomal chlorophylls. , ,,,,,,, …”
Section: Resultsmentioning
confidence: 81%
“…Recently we reported that zinc 3-hydroxymethyl-purprin 18 derivative 5 (right in Figure 1) possessing acid anhydride moiety on the exo six-membered ring instead of the natural exo fivemembered E-ring formed chlorosomal self-aggregates in aqueous media, similarly to natural BChls and synthetic models. 27 Furthermore, we have examined self-aggregation behaviors of its monodecarbonylated chlorins 6 and 7 possessing a sixmembered lactone E-ring (right in Figure 1) in a nonpolar organic solvent: 6 possessing 13-CdO self-aggregated, whereas 7 possessing 15-CdO remained monomeric. 28 We designed four porphyrins, zinc 3-hydroxymethyl-protopyropheophorbide-d derivatives 1-4 (see molecular structures in center of Figure 1) to clarify the structural requirements for chlorosomal self-aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the synthesis of zinc 3-(hydroxymethyl)-purpurin-18 and its imide derivative as novel chlorosomal chlorophyll models. [38] These chlorins bear an anhydride or imide group fixed to an expanded exo six-membered E-ring instead of a keto-carbonyl group (13-COCH 2 ) fixed to an exo five-membered E-ring and also self-aggregate to form chlorosome-like oligomers, thus indicating that the presence of 13-COX [X = OCO, N(C 6 H 13 )CO] is vital as the chlorosomal substituent. Moreover, chlorosome-like self-aggregation of synthetic porphyrins possessing three chlorosomal moieties has also been reported, [36,45] where the 13-formyl-(or keto)-carbonyl group in synthetic zinc 3 1 -hydroxyporphyrin acts as a chlorosomal substituent without the E-ring, thus suggesting that conformationally free 13-COR (R = H, CH 3 ) is also acceptable for the formation of such selfaggregates.…”
Section: Oligomeric States Of Zinc Chlorins 1-3: the 13-methoxycarbonmentioning
confidence: 99%
“…[10] The E-ring in such pigments fixes the conformation of the 13-keto-carbonyl moiety such that it achieves a robust interaction with either an amino acid residue in proteins or a functional group in other molecules. [37] Recently, we reported the selfaggregation of zinc chlorins bearing an exo six-membered ring (13,15-anhydride/imide, 13-COXCO-15 [X = O, NC 6 H 13 ]), [38] which was modified from purpurin 18 (Fischer nomenclature, 3 1 ,3 2 -didehydro-15-carboxyrhodochlorin anhydride for IUPAC IUB nomenclature [39] ). Such zinc chlorins possessing a 13-carbonyl group on an exo sixmembered E-ring self-aggregate in an aqueous medium to form chlorosome-like oligomers, thus indicating that the carbonyl groups of the anhydride and imide function on the E-ring are as suitable for constructing hydrogen-bonding networks as the usual 13-keto-carbonyl group on an exo five-membered E-ring.…”
Section: Introductionmentioning
confidence: 99%
“…In PDT, the use of light sources with wavelengths in the red or near-infrared region enables deep penetration of tissue, which in turn places a premium on photosensitizers that are active in the red or near-infrared spectral region. In more recent years, the groups of Mironov and of Pandey have significantly expanded the scope of chlorin−imides, including extension to bacteriochlorin−imides derived from bacteriochlorophyll a . The chlorin−imides have been used chiefly as photosensitizers in PDT ,, although several studies have been carried out related to artificial photosynthesis. , , Limited spectroscopic studies to date suggest that the presence of the six-membered imide ring does not significantly alter the excited-state lifetime of the chlorin…”
Section: Introductionmentioning
confidence: 99%